2019–2020 Florida Citrus Production Guide: Citrus Root Weevils - Larry W. Duncan; Catharine Mannion (EDIS)
Citrus root weevils represent a complex of species known to infest citrus trees and various alternate host plants in Florida. This 4-page fact sheet is part of the 2019–2020 Florida Citrus Production Guide. Written by Larry W. Duncan and Catharine Mannion, and published by the Entomology and Nematology Department, March 2019.